The Influence of Human Resource Competence and Good Governance on Financial Management Performance with the Internal Control System as a Moderating Variable (Empirical Study on Regional Apparatus Organizations in Ambon City Government) - Resty Hairunnisya Pulu Hattumena; Christina Sososutiksno; Kevin Hermanto Tupamahu (LP2M IAIN Palopo, 2026)
This study was conducted with the aim of providing empirical evidence regarding the influence of human resource competency and good governance on financial management performance with the internal control system as a moderating variable in OPDs in the Ambon City Government. The sampling method used in this study was the Non-Probability Sampling method with Purposive Sampling technique. The population used in this study were OPD employees in the Ambon City Government. A total of 159 questionnaires were distributed to respondents who met the criteria and could be used as samples in the study.